2021
DOI: 10.31234/osf.io/xjvtd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism and adult attachment: Issues with current measurement practices

Abstract: Attachment styles in individuals with autism are not well understood, and research into the topic is limited to date. Authors regularly utilise standardised measures to classify attachment in adulthood, and this is the case for research with neurotypical and autistic populations. Here, we argue that there may be fundamental problems with using such measures, developed for neurotypical populations, in order to quantify attachment in those with autism. Crucially, such tools may be unable to differentiate between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Rates of ASC are raised in ED samples, particularly in AN, with estimates of 20%–37% of AN patients scoring above threshold for an ASC (Westwood & Tchanturia, 2017). Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self‐report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, while the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in‐depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019; Justo‐Núñez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of ASC are raised in ED samples, particularly in AN, with estimates of 20%–37% of AN patients scoring above threshold for an ASC (Westwood & Tchanturia, 2017). Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self‐report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, while the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in‐depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019; Justo‐Núñez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of ASC are raised in ED samples, particularly in AN, with estimates of 20-37% of AN patients scoring above threshold for an ASC (Westwood & Tchanturia, 2017). Unfortunately, attachment measures have been developed using neurotypical populations, and their use in individuals with ASC, whether using interview or self-report, is problematic (Davis & Kramer, 2021) and could lead to inflated estimates of attachment insecurity in ED samples. Relatedly, whilst the attachment measures used by studies in this review were generally rated as having a low risk of bias, it should be noted that more in-depth reviews of the psychometric properties of attachment measures have identified multiple gaps in evidence for the adequacy of such properties (Jewell et al, 2019;Justo-Núñez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%